Prevalence, risk factors and associations of primary Raynaud's phenomenon: systematic review and meta-analysis of observational studies - Michael Doherty; Peter Lanyon; Weiya Zhang; Rozeena Garner; Rakesh Kumari (BMJ Open)
Objective To systematically review the literature with regard to the prevalence, incidence, risk factors and associations of primary Raynaud's phenomenon (PRP).Method A systematic review of the literature of observational studies for PRP was undertaken using five electronic databases. Any studies reporting prevalence, incidence and risk factors of PRP were collected. Relative risk or OR and 95% CI were extracted or calculated to present the association between risk factors and PRP. Random effects model was used to pool the results.Results 33 articles assessing a total of 33 733 participants were included in this analysis (2 cohort, 17 cross-sectional and 14 case–control studies). The pooled prevalence of PRP was 4.85% (95% CI 2.08% to 8.71%) in the general population. The pooled annual incidence of PRP was 0.25% (95% CI 0.19% to 0.32%). Risk factors and associations for PRP included female gender (OR=1.65, 95% CI 1.42 to 1.91), family history (OR=16.6, 95% CI 7.44 to 36.8), smoking (OR=1.27, 95% CI 1.06 to 1.53), manual occupation (OR=2.66 95% CI 1.73 to 4.08), migraine (OR=4.02, 95% CI 2.62 to 6.17), cardiovascular disease (OR=1.69, 95% CI 1.22 to 2.34) and marital status (married, OR=0.60, 95% CI 0.43 to 0.83). The definition of PRP varied considerably between studies.Conclusions This is the first systematic review of the prevalence, incidence, risk factors and associations of PRP. Further study using uniform strict criteria for the condition is required to confirm these findings, particularly the possible association with cardiovascular disease.